ANALYSIS OF THE STABILITY OF THE BURUNDIAN FINANCIAL SECTOR: APPLICATION OF THE POISSON MODEL - Nsengiyumva, Théogène (Universitas Nusa Cendana, 2025)
This study aimed to analyze the effects of Burundian banks' activities on the stability of the Burundian financial system. The data used in this study come from the Bank of the Republic of Burundi and cover the financing activity of Burundian banks for the period 2018 to 2023. By applying the fish model, the econometric results revealed highly interesting findings leading to economic policies to improve the stability of the Burundian financial sector. For illustration, the financing of short-term trade receivables has a positive effect on the stability of the Burundian financial sector, while export credit has a negative effect on the stability of the financial sector. These results reveal a low contribution from products originating in Burundi, thus contributing to the instability of the Burundian financial sector through the deterioration of the credit portfolio. To solve this problem, the Burundian government needs to put in place incentive policies aimed at developing the business sector so as to ensure not only production but also the processing of local products with high added value prior to export. Similarly, Burundian banks must comply with the prudential and non-prudential measures laid down by the central bank in order to improve the stability of the financial sector. To achieve this, Burundian banks need to design and implement more appropriate technology for exchanging borrower data in order to improve transparency and reduce fraud in credit transactions. Keywords : Financial Stability; Poisson's Law; Burundi